The Effect of Experience-Based Learning on Learning Motivation at MA Hidayatul Mubtadiin, South Lampung - Andari, An an (CV. Tripe Konsultan, 2025)
This study aimed to analyze the effect of Experience-Based Learning (EBL) on students’ learning motivation at MA Hidayatul Mubtadiin, South Lampung. The research method employed was a quantitative approach with an ex post facto design. The research subjects consisted of 22 respondents selected through purposive sampling. The research instrument was a Likert-scale questionnaire used to measure the implementation of Experience-Based Learning, which was assessed using six indicators: First-Involvement in Concrete Experience, Second-Reflective Observation, Third-Abstract Conceptualization, Fourth-Active Experimentation, Fifth-Emotional Engagement (Motivation and Enthusiasm), and Sixth-Contextual Learning (Relevance to Real Life). The Experience-Based Learning indicators were elaborated into 28 statements. Learning motivation in this study was measured using five indicators: first-Perseverance in Learning, second-Enthusiasm for Learning, third-Clear Learning Goals, forth-Interest in the Subject Matter, and fifth-Self-Confidence and Self-Efficacy. The learning motivation indicators were elaborated into 18 statements. The findings indicate that Experience-Based Learning has a positive effect on students’ learning motivation at MA Hidayatul Mubtadiin, South Lampung. The average score for the implementation of Experience-Based Learning reached 4.38 (Very Good), with the highest aspect being Emotional Engagement (4.50). Learning motivation was also categorized as Very Good (average score of 4.27), with Perseverance in Learning (4.34) as the highest aspect. These findings affirm that experiential learning can enhance students’ enthusiasm, engagement, and self-confidence, in line with Kolb’s experiential learning theory, which emphasizes the importance of concrete experience, reflection, abstract conceptualization, and active experimentation in the learning process.